159k views
2 votes
F(x) = x2 + 1

g(x) = 5-x
(f+g)(x) =
O x2 + x-4
x²+x+4
O x2-x+6
O x2 + x + 6

1 Answer

1 vote

Answer:


\boxed{(f + g)(x) = {x}^(2) - x + 6}

Given:


f(x) = {x}^(2) + 1 \\ \\ g(x) = 5 - x

To Find:


(f + g)(x) = f(x) + g(x)

Explanation:


= > f(x) + g(x) = ({x}^(2) + 1) + (5 - x) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^(2) + 1 + 5 - x\\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^(2) + 6 - x\\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^(2) - x + 6

User Bitwalker
by
5.0k points